Project Post Intensive Care eXercise (PIX): A qualitative exploration of intensive care unit survivors' perceptions of quality of life post-discharge and experience of exercise rehabilitation. (February 2015) - Walker, Wendy; Wright, Judith; Danjoux, Gerard; Howell, Simon J; Martin, Denis; Bonner, Stephen
Patients who survive critical illness often report deterioration in health related quality of life. This has not been shown to improve following post-intensive care unit (ICU) self-directed exercise. The Post Intensive Care eXercise (PIX) study demonstrated improved objectively measured fitness following a supervised exercise programme following critical illness and also suggested beneficial effects on physical and mental health. The qualitative arm of the PIX study reported here utilised focus groups to explore in more detail recovery from critical illness, quality of life following hospital discharge, perceptions of the exercise programme and it's impact on perceived well-being. Sixteen participants (eight of whom underwent the supervised exercise programme) were allocated to four psychologist lead focus groups. Themes identified after hospital discharge centred on social isolation, abandonment, vulnerability and reduced physical activity. However, patients in the exercise group described exercise training as motivating, increasing energy levels and sense of achievement, social interaction and confidence. This study adds to the sparse literature on the patient experience post critical illness. It supports the improvements in physical and mental health suggested with exercise in the PIX study and would support further research in relation to the effects of supervised exercise and rehabilitation programmes post critical illness. It recommends that future comparative outcome studies in this patient population also include interview-based assessment as part of assessment of quality of life and an individual's functional status.